Chitosan nanoparticles in gene delivery - (:unkn) unknown (Springer Berlin Heidelberg, 2016)
Gene therapy is a new alternative treatment method that involves the internalization of deoxyribonucleic acid (DNA) or ribonucleic acid (RNA) into target cells to either express or suppress the production of endogenous proteins. An efficient gene delivery system for cellular uptake of DNA is essential for gene therapy. Chitosan has been widely used as a promising non-viral carrier for gene delivery. It is a cationic polymer with free amino groups and can bind to anionic nucleic acids spontaneously. Chitosan is biocompatible and biodegradable and has low toxicity and immunogenicity. Nucleic acids can be complexed with chitosan or entrapped in chitosan nanoparticles, which include simple complexation or ionic gelation for the preparation of chitosan-DNA nanoparticles, respectively. For DNA delivery, chitosan-tripolyphosphate (TPP) nanoparticles have been widely studied. Transfection efficiency of chitosan-based DNA delivery systems depends on formulation factors such as deacetylation degree and molecular weight of chitosan, amine group of chitosan-to-phosphate group of DNA (N/P) charge ratio, pH of medium, plasmid characteristics, and serum effect (i.e., serum protein effect). The use of chitosan-DNA nanoparticles has been limited due to low aqueous solubility of chitosan and low transfection efficiency. Recently several chitosan derivatives have been developed for enhancing transfection efficiency and solubility at neutral pH. Chitosan graft copolymers were also prepared for high transfection efficiency. Chitosan-DNA-based nanoparticles can be successfully administered by parenteral, oral, intranasal, pulmonary, and dermal routes. Transfection efficiency of chitosan-DNA nanoparticles can be optimized by changing formulation parameters. © Springer-Verlag Berlin Heidelberg 2016.
Keywords: Chitosan; DNA; Gene delivery; Nanoparticles